PELATIHAN ADMINISTRASI DENGAN SISTEM IT PADA TENAGA KEPENDIDIKAN TK ABA 27 KOTALAMA - Muslikhati, Muslikhati (Lembaga Pengkajian dan Pengembangan Masyarakat, Yayasan Cahaya Mulia Mandiri, 2020)
Purpose of the Study: To find out the pattern of services starting from administrative management in the field of education. School administration is very important because it can support the smooth teaching and learning process. Method: The expected output targets from the implementation of this service activity are products in the form of: a.) Training assistance on the use of online or IT-based administrative technology in the administrative governance of TK ABA 27 Kotalama., B). Products in the form of administrative training materials, c) Products in the form of reports. Main Findings: To Increase the ability of education personnel in the process of service and orderly administration that is carried out online (online). Applications of this study: The ability of education personnel in the service process and administrative order online (online) Novelty/Originality of this study: service pattern starting from administrative management in education. School administration is very important because it can support the smooth teaching and learning process.